Spontaneous Ureteral Rupture Secondary to Obstructing Stone - Sudhir, MD, Dr. B. K. (International Journal of Innovative Research in Medical Science, 2018)
Rupture of the urinary collecting system with or without perinephric extravasation is a rare occurrence and usually known to occur following an obstructive pathology.[1,2] Here we present a case of distal 6mm calculus in otherwise normal kidney in elderly male, presenting secondary to ureteropelvic junction rupture.